Simulation of Parameters of Plasma Dynamics of a Magneto Plasma Compressor - Victor V. Kuzenov; Sergei V. Ryzhkov; Aleksey Yu. Varaksin (Applied Sciences, 2023)
The main purpose of this article is to study the features of the structure and spectral brightness characteristics of pulsed emitting discharges of the magneto plasma compressor type in dense gases over a wide range of energy–power parameters. A numerical simulation of plasma dynamic magneto plasma compressor discharge in gases is carried out. Different quasi-stationary regimes have been studied and the main characteristics have been estimated.